Developing AI-Based Educational Animated Videos for Islamic Religious Education in Junior High Schools - Muhammad Rayfansyah; Muhammad Luthfi Hamzah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to develop an Artificial Intelligence (AI)-based educational animated video as a learning medium for Islamic Religious Education (PAI), specifically on the Islamic Cultural History (SKI) topic